2014
DOI: 10.1097/mpg.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Breast‐Feeding and Weaning Practices in the DONALD Study

Abstract: Decreasing duration of full breast-feeding should encourage health care providers to further promote longer breast-feeding duration. With the constantly high consumption of commercial CF at all ages, nutritional adequacy of both homemade and commercial CF needs to be investigated closer, as does their long-term influence on health and dietary habits, for example, fruit and vegetable intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
1
23
0
4
Order By: Relevance
“…Para a compreensão da transmissão cultural das crenças e mitos alimentares, é necessário fundamentarem-se os conceitos de crença, fé, mitos e tradição (15) A maternidade vem acompanhada de alguma insegurança em relação à capacidade de alimentar e cuidar do próprio filho. Assim, alguns mitos levam à efetivação do desmame precoce do tipo: «meu leite é pouco, fraco, insuficiente»; «meu leite secou»; «peito pequeno não produz leite suficiente»; «se amamentar a mama cai»; «o leite materno não mata a sede do bebê»; «bebê não quis pegar o peito»; motivos para a introdução precoce de mamadeiras, chupetas, chás, água e sucos (17)(18)(19).…”
Section: Práticas E Crenças Populares Como Causas E Influências No Deunclassified
“…Para a compreensão da transmissão cultural das crenças e mitos alimentares, é necessário fundamentarem-se os conceitos de crença, fé, mitos e tradição (15) A maternidade vem acompanhada de alguma insegurança em relação à capacidade de alimentar e cuidar do próprio filho. Assim, alguns mitos levam à efetivação do desmame precoce do tipo: «meu leite é pouco, fraco, insuficiente»; «meu leite secou»; «peito pequeno não produz leite suficiente»; «se amamentar a mama cai»; «o leite materno não mata a sede do bebê»; «bebê não quis pegar o peito»; motivos para a introdução precoce de mamadeiras, chupetas, chás, água e sucos (17)(18)(19).…”
Section: Práticas E Crenças Populares Como Causas E Influências No Deunclassified
“…Zudem zeigen der niedrige Anteil 4 Monate ausschließ-lich gestillter Kinder und der niedrige Anteil 6 Monate lang voll gestillter Kinder, dass die WHO-Empfehlung in Deutschland für den überwiegenden Teil der Kinder nicht erfüllt wurde. Foterek et al [13] …”
Section: Introductionunclassified
“…Einige Studien untersuchten die Stillquoten, jedoch wurden diese nur auf regionaler Ebene und mit unterschiedlichen Erhebungsmethoden durchgeführt, was die Vergleichbarkeit einschränkt. Die aktuellsten, meist regionalen Studien zeigen mit 90-97 % eine relativ hohe Prävalenz von Frauen, die mit dem Stillen begannen [12][13][14][15][16][17]. Die Basiserhebung des bundesweiten Kinder-und Jugendgesundheitssurvey (KiGGS), die 2003 bis 2006 durchgeführt wurde, zeigt, dass 76,7 % der 0-bis 17-Jährigen (Geburtsjahrgänge 1986-2006) nach der Geburt jemals gestillt worden waren [18].…”
unclassified
“…This same recommendation was already proposed in a follow-up study conducted in Germany between 2008 to 2012, where the early introduction of food was a predictor of early weaning and health professionals were therefore recommended to promote the continuity of breastfeeding in these cases 20 . Another study, analyzing data from two randomized clinical trials conducted in Iceland, concluded that mothers who exclusively breastfed for six months, compared with those who introduced other foods at four months of age, had the highest total breastfeeding times, independent of the health services and breastfeeding support offered, and they were the only ones who reached the WHO breastfeeding recommendation 21 .…”
Section: Discussionmentioning
confidence: 79%